Long-range exciton transport and slow annihilation in two-dimensional hybrid perovskites - Shibin Deng (Nature Portfolio, 2020)
Two-dimensional hybrid perovskites are promising excitonic materials; however, there currently lacks understanding on exciton diffusion and annihilation. Here Deng et al. employ transient absorption microscopy to disentangle quantum-well-thickness-dependent exciton transport and annihilation in these materials.